APLIKASI ELEKTROKOAGULASI UNTUK PENGOLAHAN LIMBAH BATIK (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
Liquid waste and the problem will arise where the human activity, household liquid waste volumediscarded can reach 60% more. Industrial liquid waste is about 30 - 40%, but is always considereda contributorthe biggest environmental polluters. Until now not many industries that do waste watertreatmentto reduce the load of the pollutant produced before it is discharged into the water body.The main reason is the costoperational high enough. Preliminary processing such as aeration in areservoir pond, the addition of a few chemicals to precipitate pollutants and pollutants, especiallyheavy metals which give rise to colors and harmful ought to be done by every industry. But becauseof the continuity of production and the duration of initial waste treatment that caused theentrepreneurs are reluctant to operate the initial processing earlier. Electrocoagulation is not anew technology, but in Indonesia has not been popular in its application. This process simple andeasy to apply with good ability in clumping various impurities and pollutants, both organic andinorganic materials. In this study will be used galvalum plate. Research with a capacity of 25 Litersof treated waste, the specification of current suppliers 5 Ampere and 24 Volt. Variations of time 30,60, 90 and 120 minutes.Keywords: pengolahan limbah cair, limbah batik, elektrokoagulasi, plat elektroda, rumah batik.